2019
DOI: 10.1177/1049731519854157
|View full text |Cite
|
Sign up to set email alerts
|

Is Individual Child Play Therapy Effective?

Abstract: This article reports a systematic review of the effectiveness of individual child play therapy with children aged 4–12 on several different presenting concerns. From over 5,000 citations, 180 studies were reviewed in detail and 17 met the inclusion criteria. A wide range of results on different concerns were revealed, with effect sizes ranging from d = –0.04 to g = 3.63, though most ranged from .35 to .80. Across most concerns, play therapy was affirmed as an empirically supported therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 34 publications
0
4
0
1
Order By: Relevance
“…Consistent with all these possible contributors to change, parents mentioned parallel child and parental sessions, play, and the therapeutic focus as factors contributing to the changes experienced. All of the mentioned factors are individually associated with positive change in therapy ( Bratton et al, 2005 ; Trowell et al, 2007 ; Haugvik and Johns, 2008 ; Drisko et al, 2019 ). However, it is likely that the changes described in our study stem from the synergy of all the different parts present in TIC together .…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with all these possible contributors to change, parents mentioned parallel child and parental sessions, play, and the therapeutic focus as factors contributing to the changes experienced. All of the mentioned factors are individually associated with positive change in therapy ( Bratton et al, 2005 ; Trowell et al, 2007 ; Haugvik and Johns, 2008 ; Drisko et al, 2019 ). However, it is likely that the changes described in our study stem from the synergy of all the different parts present in TIC together .…”
Section: Discussionmentioning
confidence: 99%
“…Five meta-analysis studies support the effectiveness of play therapy interventions with children of ages 4–13 (Bratton et al, 2005; Drisko et al, 2019; LeBlanc & Richie, 2001; Lin & Bratton, 2015; Ray et al, 2015). The results indicated that children who participated in play therapy interventions showed improvement with the range of treatment effect size between 0.3 and 0.8 standard deviations, compared to children who did not participate in any interventions.…”
Section: Play Therapy In School Counselingmentioning
confidence: 99%
“…Play therapy is an empirically supported counseling modality for working with students (Drisko et al, 2019). APT (2001) defined it as "the systematic use of a theoretical model to establish an interpersonal process wherein trained play therapists use the therapeutic powers of play to help clients prevent or resolve psychosocial difficulties and achieve optimal growth and development" (p. 20).…”
Section: Play Therapy In School Counselingmentioning
confidence: 99%
“…Play therapy adalah proses terapi dengan didesain secara sistematis yang melibatkan unsur permainan di dalamnya. Tujuan umum dari play therapy adalah membantu subjek untuk dapat memecahkan permasalahannya seperti permasalahan sosial, komunikasi, dan proses belajar pada anak (Drisko et al, 2019). Pemberian intervensi play therapy berkaitan dengan pengembangan interaksi sosial, di mana tujuannya untuk meningkatkan kemampuan anak dalam mengekspresikan perasaan, mengurangi pemikiran maladaptif, meningkatkan hubungan yang adaptif dan realistis, dan meningkatkan self talk yang positif (Fazio-Griffith & Ballard, 2014).…”
Section: Intervensiunclassified